The politics of social architecture in Medellín: A reading of the Parque Biblioteca España - Deluchi, Christina (Interstices: Journal of Architecture and Related Arts, 2020)
From 2004, Medellin, Colombia’s, dramatic urban renaissance has seen architecture used as a strategic visual and material tool in the implementation of its political project, Social Urbanism. The co-opt of architecture into the city’s narrative of historic violence and its image of transformation explains its role in the changing perception of Medellin. This paper uses the Parque Biblioteca España Santo Domingo (the Spanish Library) to explore this binary perception, uncovering the spatial and symbolic characteristics of architecture distinctly connected to the city’s political and socio-cultural ambitions. Examining tensions occurring at the intersection of capital flow, governance, and mass media, the library unfolds Medellin’s landscape of power to reveal the structural changes brought on by architecture’s tectonics and its image. Dismantling the binary, the paper reconstructs the trajectory of the city’s urban development and asks: is the social impact of architecture in Medellin dislocated from the reality of its everyday conditions?